Family history of Alzheimer's disease limits improvement in cognitive function after bariatric surgery. (17th June 2014) - Alosco, Michael L; Spitznagel, Mary Beth; Strain, Gladys; Devlin, Michael; Crosby, Ross D; Mitchell, James E; Gunstad, John
Background/Objective: Bariatric surgery can reverse cognitive impairments associated with obesity. However, such benefits may be attenuated in individuals with a predisposing risk for cognitive impairment such as family history of Alzheimer's disease. Methods: In all, 94 bariatric surgery participants completed a computerized cognitive test battery before and 12 weeks after surgery. Family history of Alzheimer's disease was obtained through self-report. Results: In the overall sample, cognitive function improved in memory and attention/executive function 12 weeks post-surgery. Repeated measures showed similar rates of improvements in attention/executive function between patients with and without a family history of Alzheimer's disease. In contrast, only individuals without a family history of Alzheimer's disease exhibited post-operative improvements in memory. A family history of Alzheimer's disease was associated with greater post-surgery rates of cognitive impairment. Conclusions: Family history of Alzheimer's disease may limit post-surgery cognitive benefits. Future studies should examine whether weight loss can modify the course of cognitive decline in patients at-risk for Alzheimer's disease.